Clostridium difficile fecal toxin level is associated with disease severity and prognosis. Issue 5 (1st June 2018) - Cohen, Nathaniel A; Miller, Tamar; Na'aminh, Wasef; Hod, Keren; Adler, Amos; Cohen, Daniel; Guzner-Gur, Hanan; Santo, Erwin; Halpern, Zamir; Carmeli, Yehuda; Maharshak, Nitsan
Abstract : Background: Antibiotic‐associated colitis caused by Clostridium difficile ( C. difficile ) is the most common cause of hospital‐acquired diarrhea. The pathogenesis of C. difficile colitis is mediated by bacterial toxins. C. difficile infection (CDI) severity may be determined by the fecal level of these toxins. Objective: The objective of this article is to determine whether fecal C. difficile toxin (CDT) levels are associated with disease severity and prognosis. Methods: A cross‐sectional study of patients admitted with CDI in a tertiary center between 2011 and 2015 was conducted. Fecal CDT levels were determined by quantitative ELISA. Severe CDI was defined as a leukocyte count of > 15 × 10 3 cells/μl, creatinine levels that deteriorated by > 1.5 times the baseline level, or albumin levels < 3 g/dl. Results: Seventy‐three patients were recruited for this study. Patients with severe CDI ( n  = 47) had significantly higher toxin levels compared to patients with mild to moderate CDI ( n  = 26) (651 ng/ml (IQR 138–3200) versus 164 ng/ml (IQR 55.2–400.1), respectively; p  = 0.001). A high toxin level (>2500 ng/ml) was associated with an increased mortality rate (odds ratio 11.8; 95% confidence interval 2.5–56). Conclusions: The fecal CDT level is associated with disease severity and mortality rate. Measuring CDT levels may be an objective and accurate way to define the severity of CDI.